“Mon adorable Mécène…” Ranieri Calzabigi’s correspondence with Wenzel Anton von Kaunitz-Rietberg - Lenka Švandová Maršálková (Theatrum Historiae)
The paper focuses on presenting a unique, exceptionally rich, but still basically unprocessed correspondence from the second half of 18th century between the Count and later Prince Wenzel Anton von Kaunitz-Rietberg, a well-known and respected figure in European history, and one of his important sources of information, Italian poet, librettist, opera reformer, writer and intellectual, Ranieri de Calzabigi. The edition of the correspondence is the main ouput of the grant project Vienna „à la française“: The role of Wenzl Anton von Kaunitz-Rietberg’s Parisian stays to his Viennese cultural patronage, which is briefly presented. The main questions in case of this paper are: Calzabigi´s position within Kaunitz´s social-informational network, his sources of information and also the relationship between the Prince and the poet